Current Trends in the Management of Ballistic Fractures of the Hand and Wrist: Experiences of a High-Volume Level I Trauma Center. (March 2018) - Ghareeb, Paul A.; Daly, Charles; Liao, Albert; Payne, Diane
Background: Ballistic fractures of the carpus and hand are routinely treated in large urban centers. These injuries can be challenging due to many factors. Various treatment options exist for these complicated injuries, but there are limited data available. This report analyzes patient demographics, treatments, and outcomes at a large urban trauma center.Methods: All ballistic fractures of the hand and wrist of the patients who presented to a single center from 2011 to 2014 were retrospectively reviewed. Patient demographics, injury mechanism, treatment modalities, and outcomes were analyzed.Results: Seventy-seven patients were identified; 70 were male, and 7 were female. Average age of the patients was 29.6 years. Seventy-five injuries were low velocity, whereas 2 were high velocity. Sixty-seven patients had fractures of a metacarpal or phalanx, whereas 4 had isolated carpal injuries. Six had combined carpal and metacarpal or phalanx fractures. Thirty-six patients had concomitant tendon, nerve, or vascular injuries requiring repair. Sixty-three patients underwent operative intervention, with the most common intervention being percutaneous fixation. Sixteen patients required secondary surgery. Eighteen complications were reported.Conclusions: The majority of patients in this report underwent early operative intervention with percutaneous fixation. Antibiotics were administered in almost all cases and can usually be discontinued within 24 hours after surgery. It is important to consider concomitant nerve, vascular, or tendon injuries requiring repair. We recommend early treatment of these injuries with debridement and stabilization. Due to lack of follow-up and patient noncompliance, early definitive treatment with primary bone grafting should be considered.